Competing mechanisms on the strength of ion-irradiated Zr/Nb nanoscale multilayers: Interface strength versus radiation hardening. (15th July 2018) - Callisti, M.; Karlik, M.; Polcar, T.
Abstract: The structural stability and mechanical properties of sputter-deposited Zr/Nb nanoscale multilayers subjected to Si-ion irradiation were investigated in relation to the individual layer thickness. The interface density distribution played a major role on the nature and amount of accumulated radiation damage. The multilayer with a smaller periodicity experienced a significantly higher atomic-scale disorder and radiation hardening compared to the multilayer with thicker individual layers. In the latter case, an enhanced radiation damage tolerance was achieved due to the balance between competing deformation mechanisms. Graphical abstract: Unlabelled Image